The effect of long term physical exercises on plasma cortisol levels - Bandara, Manoj; Rathnayake, Iresha; Somasiri, Korotta Gamage (International Journal of Medicine, 2017)
Regular physical exercises have shown to improve health. Stress can cause great impact on individual’s mental health as well as physical health. Plasma cortisol is used as a biomarker to measure stress. This study was carried out to evaluate the effect of long-term physical exercises on cortisol levels in healthy young men. The study was carried out on four study groups; non–exercised control group (NE), exercised for 6 months (E6M), exercised for 18 months (E18M) and exercised for 30 months (E30M). Thirty participants who underwent regular physical exercises for different time periods were included in each exercised group. Thirty controls were also recruited. Plasma cortisol was measured using ELIZA method and compared to the patterns of plasma glucose levels. Plasma cortisol levels of all exercised groups were significantly less than that of control group (p<0.05). A significant reduction of plasma cortisol level was observed in E6M (p<0.001) and E18 M (p<0.001). Plasma cortisol level of E30M was higher than E6M and E18M but less than the control group. Plasma glucose levels followed the same pattern as cortisol. The results of this study suggest that prolong exercises favorably alters the cortisol and glucose levels indicating reduced stress levels in young adults. The study clearly indicates that the prolong exercises have positive effect on the stress marker; plasma cortisol level as well as overall health of an individual.